Τὰ Τρίκαλα στὰ τέλη τοῦ 17ου αἰώνα μὲ βάση δύο κατάστιχα κεφαλικοῦ φόρου - ΛΑΪΟΥ ΣΟΦΙΑ (Μνήμων, 2011)
This paper investigates the demographic and economic situation of the townof Trikala (Tırhala) at the end of the 17th century on the basis of two detailedOttoman registers of the capitation tax. These registers were compiled in1692/3 (1104) and 1693/4 (1105), just after the reform of 1691, which alteredthe principles of assessment and collection of the cizye tax from hearth (hane)to person (nefer). Although the data for the town of Trikala in the register of1693/4 are incomplete, possibly due to the absence of certain relevant pages,nonetheless the non-Muslim (Christians and Jews) taxable population of thetown based on the two registers amounts to 1,197 males. Since in the majorityof cases the occupation of the taxpayers is registered, the occupation of theinhabitants engaged primarily in cottage industries and comestibles is thushighlighted, as is the guild organization of certain occupations, such as grocers,saddlers and bakers.As to its town plan, Trikala considerably expanded in comparison withthe end of the 16th century. Also, the names of other neighborhoods changed,some of them ceased to exist, while others are not cited in the two registers,ostensibly because they did not include a non-Muslim population. The distinctionbetween the town proper, nefs, and the suburb, varoş, appears also in thecase of Trikala; however, the latter was not entirely Christian as is evident bythe reference to a mosque there. Finally, the register of 1693/4 includes thenames of non-Muslim taxpayers, who lived in Muslim neighborhoods and werenot yet considered permanent inhabitants.At the end of the 17th century the town of Trikala had a lively economicactivity, which attracted inhabitants from outside, and in which the guildorganization played an important role, with interconfessional contact. These resultscan be combined with other studies to show a complex and quite differentiatedevolution of the cities in the Greek lands during the Ottoman period.